Introducing a blocked procedure in nonparametric CD-CAT. - Jiahui Zhang; Yuqing Yuan; Ziying Qiu; Feng Li (PLoS ONE)
Cognitive Diagnostic Computerized Adaptive Testing (CD-CAT), in conjunction with nonparametric methodologies, is an adaptive assessment tool utilized for diagnosing students' knowledge mastery within smaller educational contexts. Expanding upon this framework, this study introduces the blocked procedure previously used in the parametric CD-CAT, enhancing the flexibility of nonparametric CD-CAT by enabling within-block item review and answer modification. A simulation study was conducted to evaluate the performance of this blocked procedure within the context of nonparametric CD-CAT across varied conditions. With increasing block size, there was a marginal reduction in pattern correct classification rate; however, such differences diminished as item quality or test length augmented. Overall, under a majority of conditions, the blocked procedure, characterized by block sizes of 2 or 4 items, allows item review within-block while attaining satisfactory levels of classification accuracy. The integration of within-block item review and answer modification with nonparametric CD-CAT fosters a more adaptive and learner-centric testing environment.